Geographical Indications-Based Environmental Protection: Legal Challenges and Sustainable Development Goals Implementation in Indonesia: Perlindungan Lingkungan Berbasis Indikasi Geografis: Tantangan Hukum dan Implementasi Sustainable Development Goals di Indonesia - Agustianto; Disemadi, Hari Sutra; Rusdiana, Shelvi; Tan, Winsherly (LITIGASI, 2025)
Geographical Indications play a crucial role as an intellectual property regime that protects unique products originating from specific regions, shaped by both human and natural factors. The presence of natural factors makes Geographical Indications a potential tool for strengthening local economies while simultaneously protecting the environment. This study aims to analyze the potential utilization of the Geographical Indications regime in Indonesia to support sustainable development, particularly in relation to environmental protection. Employing a normative legal research method supported by a statutory approach, this study examines the connection between Geographical Indications and environmental protection. The analysis reveals that despite the conceptual link between Geographical Indications and environmental sustainability, there is no normative legal support within the existing regulatory framework governing Geographical Indications. A normative construction model is proposed to facilitate the integration of environmental protection into the Geographical Indications regime, emphasizing aspects of planning, utilization, supervision, maintenance, control, and law enforcement.